Conversion of ATP to adenosine by CD39 and CD73 in multiple myeloma can be successfully targeted together with adenosine receptor A2A blockade. Issue 1 (14th May 2020) - Yang, Rui; Elsaadi, Samah; Misund, Kristine; Abdollahi, Pegah; Vandsemb, Esten Nymoen; Moen, Siv Helen; Kusnierczyk, Anna; Slupphaug, Geir; Standal, Therese; Waage, Anders; Slørdahl, Tobias S; Rø, Torstein Baade; et al.
Abstract : Background: PD1/PDL1-directed therapies have been unsuccessful for multiple myeloma (MM), an incurable cancer of plasma cells in the bone marrow (BM). Therefore, other immune checkpoints such as extracellular adenosine and its immunosuppressive receptor should be considered. CD39 and CD73 convert extracellular ATP to adenosine, which inhibits T-cell effector functions via the adenosine receptor A2A (A2AR). We set out to investigate whether blocking the adenosine pathway could be a therapy for MM. Methods: Expression of CD39 and CD73 on BM cells from patients and T-cell proliferation were determined by flow cytometry and adenosine production by Liquid chromatograpy-mass spectrometry (HPCL/MS). ENTPD1 (CD39) mRNA expression was determined on myeloma cells from patients enrolled in the publicly available CoMMpass study. Transplantable 5T33MM myeloma cells were used to determine the effect of inhibiting CD39, CD73 and A2AR in mice in vivo. Results: Elevated level of adenosine was found in BM plasma of MM patients. Myeloma cells from patients expressed CD39, and high gene expression indicated reduced survival. CD73 was found on leukocytes and stromal cells in the BM. A CD39 inhibitor, POM-1, and an anti-CD73 antibody inhibited adenosine production and reduced T-cell suppression in vitro in coculture of myeloma and stromal cells. Blocking the adenosine pathway in vivo with a combination of Sodium polyoxotungstate (POM-1), anti-CD73, and the A2AR antagonist AZD4635 activated immune cells, increased interferon gamma production, and reduced the tumor load in a murine model of MM. Conclusions: Our data suggest that the adenosine pathway can be successfully targeted in MM and blocking this pathway could be an alternative to PD1/PDL1 inhibition for MM and other hematological cancers. Inhibitors of the adenosine pathway are available. Some are in clinical trials and they could thus reach MM patients fairly rapidly.